Hand of God, mind of Man: punishment and cognition in the evolution of cooperation - Johnson, D; Bering, J (2006)
The evolution of human cooperation remains a puzzle because cooperation persists even in conditions that rule out mainstream explanations. We present a novel solution that links two recent theories. First, Johnson & Kruger (2004) suggested that ancestral cooperation was promoted because norm violations were deterred by the threat of supernatural punishment. However, this only works if individuals attribute negative life events (or a prospective afterlife) as intentionally caused by supernatural agents. A complementary cognitive mechanism is therefore required. Recently, Bering and Shackleford (2004) suggested precisely this. The evolution of "theory of mind" and, specifically, the "intentionality system" (a cognitive system devoted to making inferences about the epistemic contents and intentions of other minds), strongly favoured: (1) the selection of human psychological traits for monitoring and controlling the flow of social information within groups; and (2) attributions of life events to supernatural agency. We argue that natural selection favoured such attributions because, in a cognitively sophisticated social environment, a fear of supernatural punishment steered individuals away from costly social transgressions resulting from unrestrained, evolutionarily ancestral, selfish interest (acts which would rapidly become known to others, and thereby incur an increased probability and severity of punishment by group members). As long as the net costs of selfish actions from real-world punishment by group members exceeded the net costs of lost opportunities from self-imposed norm abiding, then god-fearing individuals would outcompete non-believers.